Antioxidant Constituents from the Bark of Aglaia eximia (Meliaceae) - Sianturi, Julinton; Farabi, Kindi; Mayanti, Tri; Harneti, Desi; Darwati,; Supratman, Unang; Awang, Khalijah; Hayashi, Hideo (Makara Journal of Science, 2016)
The genus Aglaia is a a rich source of different compounds with interesting biological activities. A part of our continuing search for novel biologically active compounds from Indonesia Aglaia plants, the ethyl acetate extract of bark of Aglaia eximia showed significant antioxidant activity. Four antioxidant compounds, kaempferol (1), kaempferol-3-O-α-L-rhamnoside (2), kaempferol-3-O-β-D-glucoside (3) and kaempferol-3-O-β-D-glucosyl-(1→4)-α-L-rhamnoside (4) were isolated from the bark of Aglaia eximia (Meliaceae). The chemical structures of compounds 1-4 were identified on the basis of spectroscopic datas including UV, IR, NMR and MS along with by comparison with those spectra datas previously reported. All compounds showed DPPH radical-scavenging activity with IC50 values of 1.18, 6.34, 8.17, 10.63 mg/mL, respectively.